ON SO_2 MEASUREMENT IN THE OCEAN ATMOSPHERE - イワサカ, ヤスノブ; ハヤシ, マサヒコ; コガ, セイジ; タナカ, ヒロシ; IWASAKA, Yasunobu; HAYASHI, Masahiko; KOGA, Seizi; TANAKA, Hiroshi (National Institute of Polar Research, 1991)
P(論文) Seasonal change in content, size, and molecular state of aerosols containing sulfur suggested that geochemical cycle of sulfure in the Antarctic atmosphere is strongly controlled by long range transport of gaseous and particulate sulfur from the sub-Antarctic ocean. Sulfur dioxide gas is a key component for study on the geochemical cycle of various gases and particles containing sulfur. A new type detector was developed to measure SO_2 in the ocean atmosphere where usually SO_2 content is at background level. This detector can measure SO_2 of 10 ppt level or lower in about 10 minutes, and will be useful to study behavior of SO_2 in a remote area which is not polluted by human activity. departmental bulletin paper